Adsorption of Cr(VI) in wastewater using magnetic multi-wall carbon nanotubes - Zhuo-nan Huang; Xiao-ling Wang; De-suo Yang (Water Science and Engineering, 2015)
Magnetic multi-wall carbon nanotubes were prepared with wet chemical treatments and characterized by a transmission electron microscope (TEM) and X-ray diffraction (XRD). They were used as adsorbents for the removal of Cr(VI) in aqueous solutions. The effects of adsorbent dosage, the concentration of Cr(VI) in aqueous solution, temperature, and pH value on the removal efficiency were studied. Results showed that the adsorption capacity of the magnetic multi-wall carbon nanotubes increased with the initial Cr(VI) concentration, but decreased with the increase of adsorbent dosage. The adsorption amount increased with contact time. The adsorption kinetics were best represented by the pseudo second-order kinetic model, and the adsorption isotherms indicated that the Langmuir model better reflected the adsorption process. The obtained calculation results for the Gibbs free energy revealed that the adsorption was a spontaneous and endothermic process. The enthalpy deviation was 3.835 kJ·mol−1. The magnetic multi-wall carbon nanotubes showed significant potential for application in adsorption of heavy metal ions.